Buccal mucosal irritation studies of sublingual apomorphine film (APL-130277) in Syrian golden hamsters. (September 2016) - Bilbault, Thierry; Taylor, Simon; Walker, Robin; Grundy, Starr L; Pappert, Eric J; Agro, Albert
Aim: Determine the potential for cheek pouch buccal mucosa irritation in hamsters following administration of apomorphine hydrochloride film (APL-130277).Methods: Three studies were conducted with Syrian golden hamsters. (First study, four hamsters received APL-130277 three times a day [TID] for 7 days. Second study, four hamsters received APL-130277 once a day [QD] for days 1–3, twice a day [BID] for days 4–7 and TID for days 8–21. Third study, 32 hamsters received either a placebo strip or APL-130277-dosed TID for 28 days). For all the studies, the macroscopic appearance of the buccal cavities was evaluated throughout the study. In the third study, all animals were necropsied on day 29, and macroscopic and histopathological examinations were performed.Results: In the first and second studies, the buccal mucosa of the cheek pouch did not show any signs of irritation. In the third study, administration of APL-130277-dosed TID for 28 consecutive days did not result in observable local irritation of the buccal mucosa.Conclusion: In all the studies, APL-130277 produced no irritation of the cheek pouch buccal mucosa.